Ответ:
Объяснение:
' заменим в правой части равенства tg2a=sin2a/cos2a
tg2a+(1/cos2a)=(sin2a/cos2a)+(1/cos2a)=(sin2a+1)/cos2a
' заменим sin2a=2sinacosa ; 1=sin²a+cos²a; cos2a=cos²a-sin²a=
'=(cosa-sina)(cosa+sina)
= (2sinacosa +sin²a+cos²a)/((cosa-sina)(cosa+sina))=
=(sina+cosa)²/((cosa-sina)(cosa+sina))=
сократим дробь на (cosa+sina)
=(sina+cosa)/(cosa-sina) ч. и т.д.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
' заменим в правой части равенства tg2a=sin2a/cos2a
tg2a+(1/cos2a)=(sin2a/cos2a)+(1/cos2a)=(sin2a+1)/cos2a
' заменим sin2a=2sinacosa ; 1=sin²a+cos²a; cos2a=cos²a-sin²a=
'=(cosa-sina)(cosa+sina)
= (2sinacosa +sin²a+cos²a)/((cosa-sina)(cosa+sina))=
=(sina+cosa)²/((cosa-sina)(cosa+sina))=
сократим дробь на (cosa+sina)
=(sina+cosa)/(cosa-sina) ч. и т.д.